2020
DOI: 10.21873/invivo.11895
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Congenital Abdominal Cystic Lesions in Newborns and Infants

Abstract: Background/Aim: In the variety of congenital abdominal cystic lesions (CACL) of different origin, ovarian cyst is the most common intra-abdominal pathology in female neonates. The prognosis and timing of treatment varies depending on the nature of CACL. This study aimed to assess the results of diagnostics and treatment of CACL. Patients and Methods: A retrospective analysis was performed of 39 cases of CACL, with the spectrum including ovarian, enteric, mesenteric and pancreatic origin. Outcome of minimally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Radiologic studies, including abdominal ultrasonography, magnetic resonance imaging or abdominal CT scan, are usually needed for antenatal or postnatal diagnosis. 12 An abdominal CT scan is recommended for postnatal diagnosis due to its ability to document the anatomical relationship with the surrounding structures. 2 As previously mentioned, the current patient had an antenatal diagnosis of duodenal atresia by ultrasound that was ruled-out postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic studies, including abdominal ultrasonography, magnetic resonance imaging or abdominal CT scan, are usually needed for antenatal or postnatal diagnosis. 12 An abdominal CT scan is recommended for postnatal diagnosis due to its ability to document the anatomical relationship with the surrounding structures. 2 As previously mentioned, the current patient had an antenatal diagnosis of duodenal atresia by ultrasound that was ruled-out postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that in case of congenital abdominal cystic lesions, a laparoscopically assisted minimal-access approach resulted in minimal risk of complications and complete recovery in all patients (17). On the other hand, a completely different approach was necessary for patients with Hirschsprung's disease (18).…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal prophylaxis introduced in HCT patients and in patients with acute leukemias in 2014-2015, slowed down the increase in incidence of fungal infections from 2016 onwards, although it did not stop it. Looking into possible activities, other options to improve the outcome of IFD might be: wider use of invasive diagnostics, treatment with reference antifungals according to recommendations [9,17], use of minimally-invasive surgery in diagnostics and treatment [32,33], or successful prophylaxis and treatment of viral infections preceding development of IFD [4,34,35]. New diagnostic methods and antifungals may appear.…”
Section: Discussionmentioning
confidence: 99%